Recent Progress of Electrospun Nanofiber-Based Composite Materials for Monitoring Physical, Physiological, and Body Fluid Signals - Guo, Fang; Ren, Zheng; Wang, Shanchi; Xie, Yu; Pan, Jialin; Huang, Jianying; Zhu, Tianxue; Cheng, Si; Lai, Yuekun (Nano-Micro Letters, 2025)
Flexible electronic skin (E-skin) sensors offer innovative solutions for detecting human body signals, enabling human–machine interactions and advancing the development of intelligent robotics. Electrospun nanofibers are particularly well-suited for E-skin applications due to their exceptional mechanical properties, tunable breathability, and lightweight nature. Nanofiber-based composite materials consist of three-dimensional structures that integrate one-dimensional polymer nanofibers with other functional materials, enabling efficient signal conversion and positioning them as an ideal platform for next-generation intelligent electronics. Here, this review begins with an overview of electrospinning technology, including far-field electrospinning, near-field electrospinning, and melt electrospinning. It also discusses the diverse morphologies of electrospun nanofibers, such as core–shell, porous, hollow, bead, Janus, and ribbon structure, as well as strategies for incorporating functional materials to enhance nanofiber performance. Following this, the article provides a detailed introduction to electrospun nanofiber-based composite materials (i.e., nanofiber/hydrogel, nanofiber/aerogel, nanofiber/metal), emphasizing their recent advancements in monitoring physical, physiological, body fluid, and multi-signal in human signal detection. Meanwhile, the review explores the development of multimodal sensors capable of responding to diverse stimuli, focusing on innovative strategies for decoupling multiple signals and their state-of-the-art advancements. Finally, current challenges are analyzed, while future prospects for electrospun nanofiber-based composite sensors are outlined. This review aims to advance the design and application of next-generation flexible electronics, fostering breakthroughs in multifunctional sensing and health monitoring technologies. Highlights: 1 This work reviews recent advancements in electrospun nanofiber-based composite materials for monitoring physical, physiological, and body fluid signals, with a particular focus on the design strategies of nanofiber-based composites. 2 The electrospinning technologies, nanofiber morphologies, fabrication of nanofiber membranes, and the integration of nanofibers with materials such as hydrogels, aerogels, or metals are comprehensively reviewed and discussed. 3 The current challenges and future prospects of nanofiber-based composite materials for human monitoring are discussed and analyzed.